Current status of ablative therapies for renal tumors - Mues, Adam C. (Medknow Publications, 2009)
The increase in detection of small (≤ 4 cm) renal cortical neoplasms has made nephron-sparing surgery the new standard of care for T1a renal lesions. Advances in minimally invasive surgery have improved the surgical approach to these lesions to include laparoscopic partial nephrectomy and renal ablative therapies. In this review, we discuss the indications, outcomes, and potential complications of the commonly used ablative modalities in urologic practice. We will expand on renal cryoablation and review the mechanism of action, surgical approaches, and evidence based medicine using this modality.